2011
DOI: 10.5172/conu.2011.240
|View full text |Cite
|
Sign up to set email alerts
|

Supporting cross-cultural communication and culturally competent care in the linguistically and culturally diverse hospital settings of UAE

Abstract: The United Arab Emirates (UAE) has become a linguistically and culturally diverse society where the majority of health care staff is drawn from a range of non-Arabic speaking backgrounds. In hospitals, the resultant mix of language and cultural differences highlights the importance of the role of nurses in facilitating the quality of care as the primary healthcare workers communicating and interacting with both patients and colleagues. Given the dearth of research in this area in the unique context of UAE, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Ineffective communication can lead to distress not only in patients and families but also in clinicians. 41,42 Differences in clinicianefamily communication according to clinicians', and patients' and families' cultures, including religious affiliations and ethnic backgrounds, may have an impact on communication interactions and end-of-life decision-making. 43 Without analysing communication practices, the findings of one study identified that withdrawal of active treatment occurred more often if physicians were of Catholic and Protestant religious affiliations than those of Jewish, Greek Orthodox, or Muslim religions.…”
Section: Discussionmentioning
confidence: 99%
“…Ineffective communication can lead to distress not only in patients and families but also in clinicians. 41,42 Differences in clinicianefamily communication according to clinicians', and patients' and families' cultures, including religious affiliations and ethnic backgrounds, may have an impact on communication interactions and end-of-life decision-making. 43 Without analysing communication practices, the findings of one study identified that withdrawal of active treatment occurred more often if physicians were of Catholic and Protestant religious affiliations than those of Jewish, Greek Orthodox, or Muslim religions.…”
Section: Discussionmentioning
confidence: 99%
“…The United Arab Emirates (UAE) has become a linguistically and culturally diverse society where the majority of health care's staff drawn from a range of non-Arabic speaking backgrounds. In hospitals, the resultant mix of language and cultural differences highlights the importance of the role of nurses in facilitating the quality of care as the primary healthcare workers communicating and interacting with both patients and colleagues, therefore in the Arab countries the presence of those health providers with their different believes and cultures needs to be evaluated and assessed [2] .…”
mentioning
confidence: 99%
“…This is a big challenge to overcome on account of the lack of op- portunities for such training and skills. 5 UAE holds a small local Emirati population, estimated as 11.5% of the total population in 2010 6 and a large expatriate population of different nationalities. Arabic is the national language, and English is widely spoken by the residents.…”
Section: Culture As a Competencymentioning
confidence: 99%